Reconstruction of energy and angle distribution function of surface-emitted negative ions in hydrogen plasmas using mass spectrometry. (7th March 2017) - Kogut, D; Achkasov, K; Dubois, J P J; Moussaoui, R; Faure, J B; Layet, J M; Simonin, A; Cartry, G
Abstract: A new method involving mass spectrometry and modeling is described in this work, which may highlight the production mechanisms of negative ions (NIs) on surface in low pressure plasmas. Positive hydrogen ions from plasma impact a sample which is biased negatively with respect to the plasma potential. NIs are produced on the surface through the ionization of sputtered and backscattered particles and detected according to their energy and mass by a mass spectrometer (MS) placed in front of the sample. The shape of the measured negative-ion energy distribution function (NIEDF) strongly differs from the NIEDF of the ions emitted by the sample because of the limited acceptance angle of the MS. The reconstruction method proposed here allows to compute the distribution function in energy and angle (NIEADF) of the NIs emitted by the sample based on the NIEDF measurements at different tilt angles of the sample. The reconstruction algorithm does not depend on the NI surface production mechanism, so it can be applied to any type of surface and/or NI. The NIEADFs for highly oriented pyrolitic graphite (HOPG) and gadolinium (low work-function metal) are presented and compared with the SRIM modeling. HOPG and Gd show comparable integrated NI yields, however the key differences in mechanisms of NI production can be identified. While for Gd the major process is backscattering of ions with the peak of NIEDF at 36 eV, in case of HOPG the sputtering contribution due to adsorbed H on the surface is also important and the NIEDF peak is found at 5 eV.